Pengaruh Murattal Terhadap Penurunan Tekanan Darah Tinggi di Posyandu Lansia Kabupaten Lampung Tengah - Andora, Novika (IJNP (Indonesian Journal of Nursing Practices), 2015)
Background : Hypertension is the third cause of death after stroke and tuberculosis, reached 6,7% of the population mortality at all ages in Indonesia. Murattal is sound of Al–Qur’an recording which is chanted by Qari’ or Al – Qur’an reader which contain verses of Al – Qur’an. Murattal is used as a media to reduce an active guanylate cyclase which causes vasodilatation and relaxation so that it can flow the blood and lower the blood pressure.Purpose: To know the diff erent of blood pressure before and after given Murattal. To know the different of blood pressure reducting between the intervention group (listen Murattal twice a day and three times a day) primarily to the control group (pharmacology drugs).Method: This research was a Quasi experimental study with less form of non – equivalent group design control. The total of respondents was 86 people, 43 people for the intervention group and 43 for the control group and the analysis used was Wilcoxon Test, Mann Whitney Test, Kruskal Willis and Friedman Test.Result: The result of Wilcoxon for intervention group and control group was 0,000. The result of Mann Whitney Test for systolic blood pressure was 0,038 and diastolic blood pressure was 0,000. The result of Kruskal Willis for systolic blood pressure was 0,025 and diastolic blood pressure was 0,00. The result of Friedman Test for intervention group was 0,000.Conclusion: Both of the intervention group and the control group could lower high blood pressure in elderly. Murattal could be used as Alternative Therapy non-pharmacological management to reduce hypertension.Keywords: Murattal, hipertension, elderly